AN INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) ENABLED KNOWLEDGE-BASED MALAY SOCIETY - A.N., Zainab; Abrizah, Abdullah; N.N., Edzan (Malaysian Journal of Library and Information Science, 2002)
Identify five conditions of an information rich society: the existence of a conducive info-structural environment, a reliable and robust ICT infrastructure, a community that is ICT literate, a community that have the necessary information skills, and the existence of supportive governance. The barriers comprise situations that are not in consonance with overall development objectives such as brain drain from developing countries to developed nations, the inability to recognize the potential of local knowledge databases, which if collated and provided widely through the ICT would increase the value and global use, the failure to apply, use or add value to existing knowledge, the lack of information skills in locating, searching and handling information; and lack of ICT skill. ICT is seen as an enabler and not the sole instrument of an information rich society. Describe studies that indicate that the Malay society is not ICT illiterate and do know the importance of IT in their daily lives. The Malays are aware of current S& T issues and readily utilize the widely available public information channels. The Internet is mainly used for communication via e-mails and searching for information. In Malaysia, a supportive governance (government and citizens) is already in place but there is the need to improve the info-structure environment and increase ICT literacy to enable a knowledge-based Malay society.